2019
DOI: 10.29359/bjhpa.11.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Level of knowledge regarding health as well as health education and pro-health behaviours among students of physical education and other teaching specialisations

Abstract: Background:The aim of the study was to assess the relationship between the level of knowledge regarding health and health education as well as the pro-health behaviours of students of physical education and other teaching specialisation. Material and methods: Anonymous and voluntary research was carried out in the years 2013--2014 among a randomly chosen group of Krakow academic youth. The research applied: involved the Inventory of Health Behaviours (IHB) (Polish: Inwentarz Zachowań Zdrowotnych) by Z. Juczyńs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Thus, the conducted research revealed the following tendency: 1) the deterioration of health state of Ukrainian students; 2) students are diverse for reasons of health; 3) the disease incidence rate of students from the same rural or urban area is dissimilar in different HEI; 4) there are differences in the health state of students from different regions; 5) targeted steps to preserve students' health and improve their lives have a positive tendency to reduce the disease incidence among youth. The results of our studies confirm the conclusions of many scientists [1,2,5,8 and others] and supplement them. , that is, the system of character traits that determine the degree of self-organization and self-education of an individual.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the conducted research revealed the following tendency: 1) the deterioration of health state of Ukrainian students; 2) students are diverse for reasons of health; 3) the disease incidence rate of students from the same rural or urban area is dissimilar in different HEI; 4) there are differences in the health state of students from different regions; 5) targeted steps to preserve students' health and improve their lives have a positive tendency to reduce the disease incidence among youth. The results of our studies confirm the conclusions of many scientists [1,2,5,8 and others] and supplement them. , that is, the system of character traits that determine the degree of self-organization and self-education of an individual.…”
Section: Discussionsupporting
confidence: 92%
“…The problem of health has always been one of the most pressing problems both at the level of scientific cognition and at the level of everyday consciousness [1,2,3]. Considering the modern integrated interdisciplinary concept of health, it combines the psychological and physiological aspects of human health.…”
Section: Introductionmentioning
confidence: 99%
“…Slovakian students have more than 6000 minutes per week [15]. Polish students have more than 9000 minutes per week [9]. Experts consider both results to be an acceptable level of weekly PA of students.…”
Section: Discussionmentioning
confidence: 99%
“…The students of the faculties of physical education and sports have an additional amount of PA at least 8-10 hours per week [23]. The IPAQ data from Polish students of sports and physical education departments shows 9500 minutes of PA per week [9]. There is a need for more precise determination of the optimal level of weekly PA of students studying in the humanities and technical faculties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation